2020
DOI: 10.1002/marc.202000067
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Polycondensation for the Synthesis of Poly(Aryl)Sulfides

Abstract: the sulfur atom in one transformation is the most desirable process, however, such a reaction is yet unprecedented. A solution to this shortcoming may be the use of hydrogen sulfide surrogates in CS cross couplings to access poly(phenyl)sulfide derivatives according to a polycondensation reaction. We and others have shown that silyl thiol, [35] thiourea [36] or potassium thioacetate [37] offer the unique access to diaryl sulfide derivatives. [36,[38][39][40][41][42] We here report the synthesis of poly(phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The SEM protection of the imidazole moieties was necessary during the whole process because of the poor solubility of the free amines. The double C−S cross‐coupling/cyclization sequence using potassium thioacetate as H 2 S surrogate [7c,f] was initiated by [Pd(dba) 2 ] and Xantphos. This ring closing reaction provided isomerically pure 3 as a dark orange solid in 86 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…The SEM protection of the imidazole moieties was necessary during the whole process because of the poor solubility of the free amines. The double C−S cross‐coupling/cyclization sequence using potassium thioacetate as H 2 S surrogate [7c,f] was initiated by [Pd(dba) 2 ] and Xantphos. This ring closing reaction provided isomerically pure 3 as a dark orange solid in 86 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, we developed a polycondensation of bifunctional benzene and thiophene derivatives, providing access to poly(phenylene) and poly(thiophenylene) sulfides [11c] . However, we found that the efficiency of the polycondensation was strongly affected by the supporting bisphosphine ligands.…”
Section: Introductionmentioning
confidence: 97%
“…[15][16][17][18][19] It is highly desired to develop concise and effective strategies for synthesizing functionalized aryl sulfides in organic and pharmic synthesis. [20][21][22][23][24] To date, numerous methods have been developed for the construction of the aromatic C-S bond, [25][26][27][28][29] and C-H activation have been widely applied in sulfidation reactions among those methods. [30][31][32][33][34] For example, transition metal catalysis is an effective protocol using C-H activation to build C-S bonds (Scheme 1, Eq.…”
mentioning
confidence: 99%